Emerging Advances in Combinatorial Treatments of Epigenetically Altered Pediatric High-Grade H3K27M Gliomas - Leszczynska, Katarzyna B.; Jayaprakash, Chinchu; Kaminska, Bozena; Mieczkowski, Jakub (Frontiers in Genetics, 2021)
Somatic mutations in histone encoding genes result in gross alterations in the epigenetic landscape. Diffuse intrinsic pontine glioma (DIPG) is a pediatric high-grade glioma (pHGG) and one of the most challenging cancers to treat, with only 1% surviving for 5 years. Due to the location in the brainstem, DIPGs are difficult to resect and rapidly turn into a fatal disease. Over 80% of DIPGs confer mutations in genes coding for histone 3 variants (H3.3 or H3.1/H3.2), with lysine to methionine substitution at position 27 (H3K27M). This results in a global decrease in H3K27 trimethylation, increased H3K27 acetylation, and widespread oncogenic changes in gene expression. Epigenetic modifying drugs emerge as promising candidates to treat DIPG, with histone deacetylase (HDAC) inhibitors taking the lead in preclinical and clinical studies. However, some data show the evolving resistance of DIPGs to the most studied HDAC inhibitor panobinostat and highlight the need to further investigate its mechanism of action. A new forceful line of research explores the simultaneous use of multiple inhibitors that could target epigenetically induced changes in DIPG chromatin and enhance the anticancer response of single agents. In this review, we summarize the therapeutic approaches against H3K27M-expressing pHGGs focused on targeting epigenetic dysregulation and highlight promising combinatorial drug treatments. We assessed the effectiveness of the epigenetic drugs that are already in clinical trials in pHGGs. The constantly expanding understanding of the epigenetic vulnerabilities of H3K27M-expressing pHGGs provides new tumor-specific targets, opens new possibilities of therapy, and gives hope to find a cure for this deadly disease.